Long-term elevated levels of loneliness are linked to lower health-related quality of life in middle-aged Australian women - Neta HaGani; Katherine Owen; Philip J. Clare; Dafna Merom; Ben J. Smith; Ding Ding (Communications Psychology)
Abstract Loneliness has long been associated with poor health outcomes. However, few studies have considered the dynamic nature of loneliness over time. This study aimed to identify longitudinal patterns of loneliness over 18 years and their associations with physical and mental health-related quality of life. Using data from the Australian Longitudinal Study of Women’s Health, we conducted a Latent Class Analysis to identify long-term loneliness patterns. We used Multinomial logistic regression to examine baseline predictors of loneliness trajectories and linear regression to examine the association between loneliness trajectories and health-related quality of life. Baseline predictors, such as smoking, depression, anxiety, stress and low social support, were associated with higher odds of ’Increasing’, ‘Stable-medium’ and ‘Stable-high loneliness. Compared to ‘Stable-low loneliness, ‘Increasing’ [B = −3.73 (95%CI = −5.42, −2.04)], ‘Medium’ [B = −3.12 (95%CI = −5.08, −1.15)] and ‘High’ loneliness [B = −5.67 (95%CI = −6.84, −4.49)] were associated with lower mental health-related quality of life. ‘Increasing’ loneliness was also associated with lower physical health-related quality of life [B = −1.06 (95%CI = −2.11, −0.02)]. Among health-related quality of life sub-scales, emotional role, social functioning and physical role were the most strongly associated with loneliness. Findings highlight the importance of addressing loneliness among women to promote their health and well-being.